TRANSFORMATION OF TAJWEED LEARNING MANAGEMENT THROUGH DIGITAL METHOD APPROACH - Widat, Faizatul; Sandi Kurniawan, Rizki (Universitas Nurul Jadid, 2023)
This study examines implementing the digital method approach in tajweed learning at MI Al-Islamiyah. This research uses a qualitative approach with a case study method. Data were collected through interviews, observation, and analysis of related documents. The transformation begins with preparing a strategic plan that includes digital content development, teacher training, and infrastructure and technology upgrades. The results showed that implementing the digital method approach has had a positive impact. Students are more enthusiastic and engaged in tajweed learning with interactive content such as videos, animations, and educational games. Teachers experience quality developments in integrating technology in tajweed learning, which positively impacts teaching quality. In addition, collaboration with parents in supporting children's tajweed learning has also increased. With the transformation of tajweed learning management through a digital approach, MI Al-Islamiyah can provide broader access for students to learn tajweed. The change of Tajweed learning management through a digital system at MI Al-Islamiyah has increased learning effectiveness, student engagement, teacher quality, and supporting collaboration with parents. Thus, the digital method approach becomes a relevant alternative to enrich and improve tajweed learning in the context of Islamic education in this digital era.